Penyuluhan dan Demo Masak dalam Upaya Pemberdayaan Ekonomi Kreatif Masyarakat sebagai Peningkatan Kesejahteraan dan Upaya Pencegahan Stunting - Muhammad Khoiruddin Al Amin; Sinta Nadziatul Izqia; Eka Zuni Astuti; Miss Nipatimoh Phudaro; Ninis Mukaromatul Hikmah; Fashara Fananda Hutami; Dea Juliana Putri; Salwa Qotrunnada; Auliya Husna; Alfithra Madya Fasa; Sevira Nurhalimah; Andi Khairunmin Alfi Syahrin; Febriani Febriani; Muhammad Isra Oktavianto; Aufaro Wiradzkia Muhammad (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Community creative economic empowerment plays an important role in improving welfare, preventing stunting, and enabling the development of creative potential and the uniqueness of local culture. The MAMAH TING-TING counselling and cooking demonstration in Sidorejo Village focused on delivering information on the prevention of wasting and stunting through the utilisation of local food, with interaction of question and answer sessions and quizzes, as well as the practice of making corn pudding as a High Calorie High Protein (TKTP) menu for the prevention of stunting in children, attended by 30 out of 40 invited PKK members. The MAMAH TING-TING counselling and cooking demonstration have successfully delivered important information about wasting and stunting prevention to the community, especially the PKK women of Sidorejo Village. Through a comprehensive explanation of the meaning, differences, causal factors, impacts, prevention and control of wasting and stunting, as well as a cooking demonstration of corn pudding as an example of a TKTP menu, participants are expected to better understand the importance of nutritious food consumption in preventing stunting in children. The interaction of question and answer sessions and quizzes have also contributed to ensuring participants' understanding of the material presented.